CHARACTERIZATION OF BASIC CANCRINITE SYNTHESIZED IN A BUTANEDIOL-WATER SYSTEM - Fechtelkord M.; Posnatzki B.; Buhl J.-C. (My University, 2003)
Na-cancrinite [ideal composition: Na8(AlSiO4)*(OH)2*8H2O] has been synthesized in a mixture of 1,3- or 1,4-butanediol and water either with direct reactants (silica sources: tetraethoxysilane, precipitated silica, alumina sources: aluminium sec-butoxide) or gels formed from tetraethoxysilane and aluminium sec-butoxide / aluminium isopropoxide with sodium hydroxide as mineralizing agent. The products were characterized by X-ray powder diffraction and FTIR spectroscopy at room temperature and elevated temperatures up to 1073K, coulometric and carbon titration, thermogravimetry, scanning electron microscopy and 29Si, 23Na and 27Al MAS NMR spectroscopy, as well as 1H and {1H}13C CPMAS NMR spectroscopy. The X-ray powder patterns show cancrinite as the only phase in all samples. The spectroscopic and analytic investigations mainly suggest the presence of both molecular water and hydroxyl anions beside small impurities of carbonate. X-ray diffraction of all samples at elevated temperatures indicates decomposition temperatures in the range between 933 and 1003K. The structure refinement of a selected sample in the hexagonal space group P 63 reveals a hydroxylcancrinite with lattice parameters a 0 = 12.7558(3)Å and c 0 = 5.1985(2)Å with R = 0.0107, Rp wp = 0.0161, and R (F2) = 0.0373. The structure is characterized by water molecules and hydroxyl anions occupying two 6c positions and one 2a position, coordinating sodium in the channel.